Pengaruh Pengalaman Kerja, Kompensasi dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Maybank Cabang Semarang - Wardani, Vina Ayu Kusuma; Liana, Lie (Universitas Batanghari, 2024)
This study aims to analyze the effect of work experience, compensation and work motivation on employee performance. This research is a quantitative research with the object of research on employees of PT Maybank Semarang Branch. The population in this study were all employees of PT Maybank Semarang Branch was 82 respondents. The data collection method used a questionnaire in the form of a google form distributed to all respondents. Data analysis in this study used respondent description test, variable description, validity test, reliability test, F test, determination coefficient test (RÂ²) and hypothesis testing results. The results of this study indicate that work experience has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance, and work motivation has a positive and significant effect on employee performance.